Effect of platelet rich fibrin on edema and pain following third molar surgery: a split mouth control study - Uğur Gülşen; Mehmet Fatih Şentürk (BMC, 2017)
Abstract Background To evaluate the efficacy of platelet-rich fibrine (PRF) on postoperative edema and pain after impacted mandibular third molar surgery. Methods The prospective study was comprised 30 patients who presented for the removal of bilateral impacted mandibular third molar teeth. After extraction, the sockets were filled with PRF or without PRF in the study and control groups, respectively. Postoperative edema was measured with a flexible tape measure by calculating the distance between several facial landmarks on postoperative days two and seven. Postoperative pain was evaluated with a line-type visual analogue scale (VAS) and a verbal scale (VRS). SPSS version 20.0 was used for data analysis. Results Both groups recorded significant improvement compared to the baseline levels in almost all of the outcome variables. There was no statistically significant difference between the study and control groups (p > 0.05). Conclusions Using or not using PRF to reduce postoperative pain and edema in third molar surgery was equally successful. Trial registration This study was retrospectively registered at the ISRCTN registry ( ISRCTN16849867 ) on 6 March 2017.